Stress response in Rhodococcus strains - Pátek, Miroslav; Grulich, Michal; Nešvera, Jan (Biotechnology advances, 2021)
Rhodococci are bacteria which can survive under various extreme conditions, in the presence of toxic compounds, and in other hostile habitats. Their tolerance of unfavorable conditions is associated with the structure of their cell wall and their large array of enzymes, which degrade or detoxify harmful compounds. Their physiological and biotechnological properties, together with tools for their genetic manipulation, enable us to apply them in biotransformations, biodegradation and bioremediation. Many such biotechnological applications cause stresses that positively or negatively affect their efficiency. Whereas numerous reviews on rhodococci described their enzyme activities, the optimization of degradation or production processes, and corresponding technological solutions, only a few reviews discussed some specific effects of stresses on the physiology of rhodococci and biotechnological processes. This review aims to comprehensively describe individual stress responses in Rhodococcus strains, the interconnection of different types of stresses and their consequences for cell physiology. We examine here the responses to (1) environmental stresses (desiccation, heat, cold, osmotic and pH stress), (2) the presence of stress-inducing compounds (metals, organic compounds and antibiotics) in the environment (3) starvation and (4) stresses encountered during biotechnological applications. Adaptations of the cell envelope, the formation of multicellular structures and stresses induced by the interactions of hosts with pathogenic rhodococci are also included. The roles of sigma factors of RNA polymerase in the global regulation of stress responses in rhodococci are described as well. Although the review covers a large number of stressful conditions, our intention was to provide an overview of the selected stress responses and their possible connection to biotechnological processes, not an exhaustive survey of the scientific literature. The findings on stress responses summarized in this review and the demonstration of gaps in current knowledge may motivate researchers working to fill these gaps.
Keywords: Starvation; Biodegradation; biotransformace; Stress; Biotransformation; Stress, Physiological; Biotechnology; Rhodococcus; fyziologický stres; biodegradace; Environment; biotechnologie; Cell aggregation; Biofilm; Biodegradation, Environmental; Sigma factors; Toxic compounds